595 LOW INCIDENCE OF ARRHYTHMIC SYNCOPE AND PACEMAKER IMPLANTATION IN OLDER PATIENTS WITH BIFASCICULAR BLOCK AND IMPLANTABLE CARDIAC MONITOR. (15th December 2022) - Gambardella, Marco; Fumagalli, Carlo; Rafanelli, Martina; Brignole, Michele; Guarducci, Caterina; Bettoni, Niccolò; Pieragnoli, Paolo; Casolaro, Flavia; Paolisso, Giuseppe; Marfella, Raffaele; Sardu, Celestino; Ungar, Andrea
Abstract: Background: In patients with unexplained syncope, bifascicular block (BFB) is considered associated with syncope due to either heart block or sinus arrest. Immediate or delayed pacemaker (PM) implantation after ECG documentation of syncopal recurrence by means of implantable cardiac monitors (ICM) is still debated. We aimed to assess the incidence of recurrent syncope and guideline-based PM implantation in patients with syncope and BFB implanted with ICM. Methods: Consecutive patients with syncope and BFB followed at two tertiary care syncope units and implanted with ICM from 2012 to 2020 were retrospectively reviewed. Only patients with >2 clinical visits and >18 years of age were included. Incidence of a Class I indication for PM implantation was the primary outcome. Results: Of 635 syncope patients implanted with an ICM, 55 (8.7%) had a BFB and were included. Median age at implantation was 75 [interquartile range, IQR:64-81] years, and 28(49.1%) were women. At 26 [IQR:12-41] months follow-up, 20 (36.3%, 16.3%/year) patients experienced syncope: in 6(10.9%) patients syncope was classified 'arrhythmic' with a higher prevalence in older individuals (p=0.048). PM implantation (N=14, 25.5%) was more frequent in patients >75 years (p=0.024). At survival analysis, patients >75 years were at highest risk of arrhythmic syncope and guideline directed PM implantation (Hazard Ratio: 4.5, 95% Confidence Intervals 1.5-13.3). Conclusions: Most older patients with syncope who received an ICM didn't have events during follow-up. Only one-in-three experienced syncope, and an even smaller number had an arrhythmic syncope with indication for PM implantation. Older age was strongly associated with PM implantation.